2010
DOI: 10.1510/icvts.2009.219568
|View full text |Cite
|
Sign up to set email alerts
|

Medium to long-term clinical outcome following stentless aortic valve replacement: comparison between allograft and xenograft valves

Abstract: The xenograft stentless valve was designed to emulate the haemodynamic performance of the allograft. Early outcomes using either surgical option (stentless xenograft valve or allograft) have been similar. However, follow-up outcomes remain to be compared. Between 1st January 1991 and 1st January 2001, 415 patients underwent aortic valve replacement. Two hundred and seventeen patients received an allograft and in 198 patients a Toronto stentless porcine valve (TSPV) was implanted. Mean time to follow-up was 6.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Thirty-five studies 7,12,13,[17][18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34]36,39,40,[45][46][47][48][49][50][51]53,[55][56][57][58][59]…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five studies 7,12,13,[17][18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34]36,39,40,[45][46][47][48][49][50][51]53,[55][56][57][58][59]…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Twenty-five studies 7 12 13 18 20 23 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 reported on the prevalence of a concomitant CABG, which included a total of 16,095 patients. A concomitant CABG was performed in a total of 5,581 (34.7%) patients.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In young adults it appears that stentless valves may have similar clinical performance to homografts during follow up ( 62 , 63 ). The differences between stented and stentless valves are less clear.…”
Section: Comparing Available Surgical Optionsmentioning
confidence: 99%
“…The pig is an important species as a food source in animal agriculture and as a large animal disease and injury model in the biomedical arena [1][2][3][4]. To further the agricultural and biomedical utility of pigs, great efforts have been made to genetically manipulate these animals through the development of technologies such as somatic cell nuclear transfer (SCNT) [2,5,6].…”
Section: Introductionmentioning
confidence: 99%